2008
DOI: 10.1200/jco.2007.15.8634
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Gemcitabine-Based Chemoradiation for Patients With Resectable Adenocarcinoma of the Pancreatic Head

Abstract: Preoperative gemcitabine-based chemoradiation followed by restaging and evaluation for surgery separated the study population into two different subsets: patients likely to benefit from PD (n = 64) and those in whom surgery would be unlikely to provide clinical benefit (n = 22). Furthermore, the encouraging overall survival observed in this large trial supports the continued investigation of gemcitabine-based preoperative therapy in resectable pancreatic cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
494
4
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 672 publications
(513 citation statements)
references
References 23 publications
9
494
4
6
Order By: Relevance
“…For the patient who had a prior history of breast cancer, the diagnosis of PDA on pancreatic FNA was based on the different tumor morphology, no other site of breast cancer metastasis at the time of pancreatic FNA, and increase serum level of carbohydrate antigen 19.9 (76 U/ ml). Among the 11 patients, five patients received systemic chemotherapy with gemcitabine and cisplatin followed by gemcitabine-based chemoradiation (Gem-Cis-XRT) as reported by Varadhachary, G.R., et al [8]; three patients received gemcitabine-based chemoradiation protocol as reported by Evans D. B. et al [7] and the remaining three patients received 5-fluorouracil-based chemoradiation [15] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the patient who had a prior history of breast cancer, the diagnosis of PDA on pancreatic FNA was based on the different tumor morphology, no other site of breast cancer metastasis at the time of pancreatic FNA, and increase serum level of carbohydrate antigen 19.9 (76 U/ ml). Among the 11 patients, five patients received systemic chemotherapy with gemcitabine and cisplatin followed by gemcitabine-based chemoradiation (Gem-Cis-XRT) as reported by Varadhachary, G.R., et al [8]; three patients received gemcitabine-based chemoradiation protocol as reported by Evans D. B. et al [7] and the remaining three patients received 5-fluorouracil-based chemoradiation [15] (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…In a phase II trial of 86 enrolled patients who received neoadjuvant gemcitabine-based chemoradiation, two patients were reported to have pCR in their subsequent pancreatectomy specimens [7]. Another study from Germany [24] reported pCR in three of 38 patients (7.9%) with locally advanced PDA who received neoadjuvant chemoradiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 Increasing numbers of patients will probably receive preoperative chemotherapy in the future. Therefore, methods that effectively prevent obstruction in the long term are needed.…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients after complete resection is poor, and more than 50% of patients develop tumor recurrence at distant or locoregional sites, with an estimated 5-year survival of only 20% (Kayahara et al, 1993;Nitecki et al, 1995;Staley et al, 1996;Sener et al, 1999;Li et al, 2004). The addition of chemotherapy and/or radiotherapy to surgical resection is important (Rothenberg et al, 1996;Oettle et al, 2007;Evans et al, 2008), however, the clinical response rate remains still unsatisfactory (Burris et al, 1997).…”
Section: Introductionmentioning
confidence: 99%